2000
DOI: 10.1161/01.atv.20.10.2243
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Oxidized Low Density Lipoprotein Levels

Abstract: Abstract-Recent studies have established oxidative modification of low density lipoprotein (LDL) as an important atherogenic factor. We examined the clinical relevance of circulating oxidized LDL (OxLDL) levels in atherosclerotic disease by an enzyme immunoassay with use of specific antibodies against OxLDL (FOH1a/DLH3) and apolipoprotein B. Plasma OxLDL levels were significantly higher in patients with coronary heart disease (nϭ65) than in control subjects (nϭ181; 201.3Ϯ11.2 versus 112.4Ϯ3.3 U/dL, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
128
0
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 365 publications
(142 citation statements)
references
References 35 publications
10
128
0
3
Order By: Relevance
“…8 In another study, plasma levels of oxidized LDL were significantly higher in patients with CHD than in controls, and were not correlated with other major risk factors. 9 Natural antioxidants (ie, ␤-carotene, vitamin C, and vitamin E) have been used as a potential strategy to reduce damage caused by oxidized LDL in patients with or at high risk for CHD, but the majority of clinical trials have not shown reductions in CHD events with this approach. 10 More clinically reliable markers of oxidative stress or the development of more effective antioxidant therapies might make this strategy more useful.…”
Section: Inflammatory Mechanismsmentioning
confidence: 99%
“…8 In another study, plasma levels of oxidized LDL were significantly higher in patients with CHD than in controls, and were not correlated with other major risk factors. 9 Natural antioxidants (ie, ␤-carotene, vitamin C, and vitamin E) have been used as a potential strategy to reduce damage caused by oxidized LDL in patients with or at high risk for CHD, but the majority of clinical trials have not shown reductions in CHD events with this approach. 10 More clinically reliable markers of oxidative stress or the development of more effective antioxidant therapies might make this strategy more useful.…”
Section: Inflammatory Mechanismsmentioning
confidence: 99%
“…Given the clinical atherogenic role of oxidized-low density lipoprotein (ox-LDL) numerous efforts have been made to detect its level in circulation. Hasegawa and workers (4), Toshima et al (5) have developed immunological technique like sandwich-ELISA. Though the major obstacle of these techniques is the difficulty in detecting the minute amount of ox-LDL, and lack of specificity of the antibody, due to the large size of apoprotein B.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that LOX-1 binds to oxidized LDL [31], and increases in oxidized LDL levels of expression are indicative of cardiovascular dysfunction [18]. We therefore analyzed LOX-1 mRNA expressions in the hearts of the transgenic mice, but no difference in their levels of expression was observed (data not shown).…”
Section: Discussionmentioning
confidence: 93%